PENCEGAHAN TINDAK PIDANA DALAM AKSI UNJUK RASA BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 1998 TENTANG KEMERDEKAAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM DI WILAYAH HUKUM KEPOLISIAN RESORT KOTA PEKANBARU - Oktavianus, Jeffry Martunas; Effendi, Erdianto; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The independence of deliver opinion in public is a rightful authority every Indonesian citizen that written in Constitution Oof Republic Indonesian 1945 in Section 28 E Subsection 3, in addition to the independence of deliver opinion arranged further in Constitution Number 9 in 1998 about The Independence Of Deliver Opinion In Public Section 1 Subsection 1.However, not infrequently of demonstration were ended chaosly and anarchist, because of less pasification and coordination with police. The purpose of this thesis are : first, to find out the prevention of criminal act in demonstration, second,to find out police obstruct in prevention of criminal act in demonstration, the third, to find out the police efforts in content of prevention obstruct criminal act factors in demonstration.The design that used of this thesis was research sociological. In the thesis, the researcher did this research about the occur of positif law in prevention th criminal act in demonstration based on Constitution Number 9 In 1998 about The Independence Of Deliver Opinion In Public.The result of this research could conclude that prevention the criminal act not only did by police, but also the nitisen who did the demonstration to obedient the certainty of rules that obtained, the lack of awareness of nitizen who did demonstration to obedient the certainty of legislation became constant for police in did the prevention of criminal act, so the police have to do efforts of preemptive, preventive, and repressive in copewith.Keyword : demonstration - criminal act - prevention